2010
DOI: 10.1590/s0104-42302010000200019
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de um programa para profilaxia de tromboembolismo venoso em pacientes clínicos em quatro hospitais de Salvador

Abstract: Resumo objetivo. Implementar um programa hospitalar de profilaxia de TEV através da criação de uma comissão, da realização de palestras e da distribuição de algoritmos baseados na Diretriz Brasileira para Profilaxia de TEV em Pacientes Clínicos e avaliar seu impacto na adequação da utilização de profilaxia em quatro hospitais de Salvador, Bahia. métodos. Foram realizados dois estudos de corte-transversal, um antes e um depois da implementação do programa, e comparadas as proporções de pacientes em risco de TEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
0
12
0
12
Order By: Relevance
“…In Brazil, studies conducted in the cities of São Paulo ( 21 ) and Salvador ( 22 ) showed that the distribution of written guidelines for physicians was not effective in increasing adherence to prophylactic measures. A meta-analysis that evaluated the effectiveness of different strategies to increase adherence to prophylactic measures for VTE also showed that passive measures, such as the distribution of guidelines, were ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, studies conducted in the cities of São Paulo ( 21 ) and Salvador ( 22 ) showed that the distribution of written guidelines for physicians was not effective in increasing adherence to prophylactic measures. A meta-analysis that evaluated the effectiveness of different strategies to increase adherence to prophylactic measures for VTE also showed that passive measures, such as the distribution of guidelines, were ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that other hospitals in Brazil should consider implementing a CDSS to increase the use of VTE prophylaxis, given that studies evaluating the use of non-computerized protocols have shown that such protocols provide no benefit. ( 21 , 22 ) …”
Section: Discussionmentioning
confidence: 99%
“…O desenho do estudo foi transversal, com avaliação da tromboprofilaxia antes e após a intervenção. Os autores concluíram que a tromboprofilaxia é subutilizada em hospitais brasileiros e que a estratégia de divulgação e programa de educação continuada são insuficientes para melhorar a indicação correta da tromboprofilaxia 75 .…”
Section: Proposta Do National Institute For Clinical Excelenceunclassified
“…Over the last 20 years, studies have been conducted to determine the situation in Brazilian hospitals with relation to VTE prophylaxis and the findings show that among both medical and surgical patients appropriate prophylactic measures are not being taken, even when risk factors for VTE are present. [7][8][9][10][11] However, few studies have been conducted with the objective of formulating strategies and providing guidance in the form of hospital-wide thromboprophylaxis programs. 11,12 Machado 13 recommends that a multidisciplinary team should be assembled made up of people who understand the importance of pharmacological prophylaxis, in order to improve the frequency and quality of provision of VTE prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] However, few studies have been conducted with the objective of formulating strategies and providing guidance in the form of hospital-wide thromboprophylaxis programs. 11,12 Machado 13 recommends that a multidisciplinary team should be assembled made up of people who understand the importance of pharmacological prophylaxis, in order to improve the frequency and quality of provision of VTE prophylaxis. 14,15 In turn, a study published by Rocha et al 11 proposed that a commission should be created in all hospitals with a mission to encourage VTE prophylaxis using educational lectures.…”
Section: Introductionmentioning
confidence: 99%